2013
DOI: 10.1021/ja4025337
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Synthesis of Pyrroloindolines via a Rhodium(II)-Catalyzed Annulation of Indoles

Abstract: Herein we report the synthesis of pyrroloindolines via a catalytic enantioselective formal [3+2] cycloaddition of C(3)-substituted indoles. This methodology utilizes 4-aryl-1-sulfonyl-1,2,3-triazoles as carbenoid precursors and the rhodium(II)-tetracarboxylate catalyst Rh2(S-PTAD)4. A variety of aryl-substituted pyrroloindolines were prepared in good yields and with high levels of enantioinduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
91
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(91 citation statements)
references
References 64 publications
0
91
0
Order By: Relevance
“…For this designed reaction pathway, the most important competitive pathway is a two-component [3 + 2] cycloaddition that has been illustrated by Spangler et al . ( 47 ) for the efficient synthesis of pyrroloindoline architectures 5 via the combination of C(3)-substituted indole 2 and Rh(II)-associated 1-sulfonyl-1,2,3-triazoles (Scheme 2B). The authors suggested that the reaction was promoted via zwitterionic-type intermediate F from an α-imino rhodium carbene species.…”
Section: Resultsmentioning
confidence: 99%
“…For this designed reaction pathway, the most important competitive pathway is a two-component [3 + 2] cycloaddition that has been illustrated by Spangler et al . ( 47 ) for the efficient synthesis of pyrroloindoline architectures 5 via the combination of C(3)-substituted indole 2 and Rh(II)-associated 1-sulfonyl-1,2,3-triazoles (Scheme 2B). The authors suggested that the reaction was promoted via zwitterionic-type intermediate F from an α-imino rhodium carbene species.…”
Section: Resultsmentioning
confidence: 99%
“…81 , Scheme 14). 40 In this reaction, the 4-aryl-1-sulfonyl-1,2,3-triazole serves as a precursor to a Rh-bound carbenoid. The authors speculate that the reaction proceeds through cyclopropanation of the indole C2-C3 bond to give 82 , followed by fragmentation of the cyclopropane and cyclization to form the dihydropyrrole ring.…”
Section: Pyrroloindoline Synthesis Via 33-disubstituted Oxindolesmentioning
confidence: 99%
“…1,2 Serving as precursors for iminocarbenes, they have found widespread applications in the synthesis of biologically valuable heterocyclic compounds, such as imidazoles and pyrroles, via cycloaddition of nitriles, 3 alkynes, 4,5 allenes, 6 furans, 7 indoles, 8 and alkenes. 9 Accordingly, finding efficient synthesis methods of N-sulfonyltriazoles from easily accessible starting materials is a continuous necessity.…”
mentioning
confidence: 99%